2020
DOI: 10.48550/arxiv.2010.02754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Particle dynamics around a dyonic charged black hole

Saeed Ullah Khan,
Jingli Ren

Abstract: In this article, we study the circular motion of particles and the well-known Penrose mechanism around a Kerr-Newman-Kasuya black hole spacetime. The inner and outer horizons, as well as ergosurfaces of the said black hole, are briefly examined under the effect of spin and dyonic charge. Moreover, by limiting our exploration to the equatorial plane, we discuss the characteristics of circular geodesics and investigate both photons, as well as marginally stable circular orbits. It is noted that black hole charge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…After the discovery of Einstein's General relativity theory [1], black holes (BHs) investigations caught a considerable interest of many researchers [2,3,4,5,6]. This theory explains how gravitational field affects the relation of time and space, as well as how quickly could an observer observed change in an object.…”
Section: Introductionmentioning
confidence: 99%
“…After the discovery of Einstein's General relativity theory [1], black holes (BHs) investigations caught a considerable interest of many researchers [2,3,4,5,6]. This theory explains how gravitational field affects the relation of time and space, as well as how quickly could an observer observed change in an object.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that the Randall-Sundrum braneworld spacetimes can be stable against perturbations [18]. Recently, Khan et al [?,20] examined the motion of geodesics in the background of braneworld Kerr and a dyonic charged spacetimes, while Deng explored the periodic orbits near a braneworld BH under the influence of tidal charge [21].…”
Section: Introductionmentioning
confidence: 99%